Modeling the Barriers of the Resilient Supply Chain: A Fuzzy-Dematel Approach - Yadav A.K.; Samuel C. (My University, 2025)
In the present era of vulnerabilities, the concept of the resilient supply chain has appeared to be the most promising and efficient tool to adapt and recover from significant disruptions. Though enormous research is available regarding the capabilities and practices that enable the resilient supply chain's success, little consideration is given to the barriers that inhibit its successful implementation in the actual scenario. In this research, we have identified 14 critical barriers to resilient supply chain in the context of the Indian manufacturing supply chain. Further, we have used an integrated Fuzzy-DEMATEL approach to evaluate these barriers. The findings reveal that lack of managerial commitment is among the most influencing barriers to the resilient supply chain, followed by poor risk awareness and poor information sharing. This research enables the academicians to understand the resilient supply chain's various capabilities, practices and barriers and provides a novel approach for quantitative analysis of the subjective parameters. Moreover, the findings enable the supply chain practitioners to allocate the resources and capabilities that mitigate the barriers and make the supply chain genuinely resilient. © 2022 World Scientific Publishing Company.